Implementation of Group Activity Therapy: Hypertension Exercise for the Elderly at UPT PSTW Jember: Penerapan Terapi Aktivitas Kelompok Senam Hipertensi pada Lansia di UPT PSTW Jember - Kurniyawan, Enggal Hadi; Siska Amaylia Putri; Prasita Kusumaningtyas; Maulidatus Sa’adah; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Tri Afandi, Alfid; M. Nur Khamid (KHD Production, 2026)
The elderly are individuals aged over 60 years. Hypertension is a condition characterized by an increase in systolic blood pressure equal to or greater than 140 mmHg and diastolic blood pressure equal to or greater than 90 mmHg. In the elderly, one of the physiological changes that occurs is a decline in cognitive function. The cognitive system refers to functions involved in thinking, remembering, learning, reasoning, and problem-solving processes. Based on screening results conducted by students at UPT PSTW Puger Jember, specifically in Wisma Teratai and Wisma Cempaka, 14 out of 20 elderly residents were found to have high blood pressure. The activities implemented included a pre-implementation stage, which involved measuring blood pressure before performing hypertension exercises. This was followed by health education related to hypertension and the hypertension exercise session itself. The final stage was the evaluation phase, which involved measuring blood pressure again after the exercise. The Group Activity Therapy (GAT) for hypertension exercise was carried out to help the elderly prevent high blood pressure and maintain it within a normal range.